MEMBANGUN MASYARAKAT PLURALIS PERSPEKTIF FARID ESACK DALAM KONTEKS POLITIK PRAKTIS DI INDONESIA - Firdaus Ainul Yaqin (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
This study aims to thoroughly explore the concept of a pluralist society from the perspective of Farid Esack in the context of practical politics in Indonesia. Religious diversity is a real event that cannot be denied in the nation and state. So that the existence of religious diversity is a gift that must be grateful for, even though all are challenges that must be faced by the people. The author uses Farid Esack's thinking because he sees Farid's history in different cultures, races, and religions. This research method is literature review or literature review. Data collection techniques with document studies, and data analysis using qualitative methods. Building a pluralist society with farid esack perspective in the context of practical politics in Indonesia can be done with pluralist concepts and hermeneutics.Keywords: Farid Esack, pluralist society, political perspective